Impact of Heart Rate on Pulsatile Hemodynamic Performance in a Neonatal ECG‐Synchronized ECLS System. Issue 1 (28th August 2018) - Wang, Shigang; Moroi, Morgan K.; Force, Madison; Kunselman, Allen R.; Ündar, Akif
Abstract: The experimental circuit consisted of an i‐cor diagonal pump, a Medos Hilite 800 LT oxygenator, an 8Fr Biomedicus arterial cannula, a 10Fr Biomedicus venous cannula, and six feet of 1/4 in ID tubing for arterial and venous lines. The circuit was primed with lactated Ringer's solution and packed red blood cells (hematocrit 40%). Trials were conducted at various heart rates (90, 120, and 150 bpm) and flow rates (200, 400, and 600mL/min) under nonpulsatile and pulsatile mode with pulsatile amplitudes of 1000–4000rpm (1000 rpm increments). Real‐time pressure and flow data were recorded for analysis. The i‐cor pump was capable of creating nonpulsatile and electrocardiography (ECG)‐synchronized pulsatile flow, and automatically reducing pulsatile frequency by increasing the assist ratio at higher heart rates. Reduced pulsatile frequency led to lower hemodynamic energy generation but did not affect circuit pressure drop. Pulsatile flow delivered more hemodynamic energy to the pseudopatient when compared with nonpulsatile flow. The pump generated more hemodynamic energy with higher pulsatile amplitudes. The i‐cor pump can automatically adjust the pulsatile assist ratio to create pulsatile flow at higher heart rates, although this caused some hemodynamic energy loss. Compared with nonpulsatile flow, pulsatile flow generated and transferred more hemodynamic energy to the neonate during ECLS (200–600mL/min), especially at high pulsatile amplitudes and low flow rates.